PENGARUH LINDUNG NILAI, FINANCIAL LEVERAGE, CORPORATE SOCIAL RESPONSIBILITY DAN KEPEMILIKAN INSTITUSIONAL TERHADAP AGRESIVITAS PAJAK - Astri Maulianti; Raja Adri SatriawanSurya; Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aims to analyze the impact of hedging, financial leverage,corporate social responsibility and institutional ownership on tax aggressiveness,.The population in this research is company listed in Indonesia Stock Exchnage in2013 until 2017. Total sample in this research is 28 companies with five yearsobservation. Sampling technique in this research using purposive samplingtechnique and analysis teqhnique using multiple liniear regression The result ofthis research indicates that financial leverage, corporate social responsibility andinstitutional ownerships influence the tax aggressiveness. Meanwhile the hegdinghas no significant impact on tax aggressiveness. Keywords: Hedging, Financial Leverage, Corporate Social Responsibility,Institutional Ownership, Tax Aggressiveness.